The role of work-related needs in the relationship between job crafting, burnout and engagement - Fabrice Travaglianti; Audrey Babic; Isabelle Hansez (SA Journal of Industrial Psychology, 2016)
Orientation: Knowing that it is imperative to better understand the antecedents and consequences of needs-supplies fit, the present research had two main objectives. Firstly we wanted to extend our knowledge about traditional psychological needs, for example highlighted through the Self-Determination Theory, by presenting more specific work-related needs. Secondly, following the new directions of organisational fit theories, we wanted to better understand how individuals make sense of fit.